Use of autologous bone grafting from the calcaneus and interconnected porous hydroxyapatite ceramic for bone transplantation in rheumatoid foot surgery. (21st June 2018) - Hirao, Makoto; Ebina, Kosuke; Etani, Yuki; Tsuboi, Hideki; Noguchi, Takaaki; Tsuji, Shigeyoshi; Hashimoto, Jun; Yoshikawa, Hideki
Cancellous bone grafts from the calcaneus have been used for the foot and ankle as well as iliac bone graft; however, there is a sparse report for calcaneal bone transplantation in the field of rheumatoid foot surgery. In this study, safety and usefulness of calcaneal bone grafts, and combination with interconnected porous hydroxyapatite ceramic, was evaluated in rheumatoid arthritis foot surgeries. Of six rheumatoid arthritis cases, three (talo-navicular joint fusion) used a calcaneal bone graft alone, and the remaining three cases (subtalar joint and talo-navicular joint fusion) used a combination of calcaneal bone graft and interconnected porous hydroxyapatite ceramic augmented with dense calcium hydroxyapatite for subtalar bony defect (1.5–2.0 cm) after the correction. Pre- and postoperative Japanese Society for Surgery of the Foot rheumatoid arthritis foot ankle scale scores were obtained for the clinical assessment. As radiographic assessment, tibio-calcaneal angle, calcaneal pitch, talo-1st metatarsal angle, and pronated foot index were also evaluated. After starting weight-bearing or walking, there was no pain and skin trouble at the fusion and harvesting sites. All cases achieved bony fusion within 6–10 weeks. Japanese Society for Surgery of the Foot rheumatoid arthritis foot ankle score was improved in all six cases. Furthermore, tibio-calcaneal angle, talo-1st metatarsal angle, and pronated foot index were also improved at latest follow-up in all cases. In conclusion, autologous bone grafting from the calcaneus was safe and convenient even in rheumatoid foot surgeries. For larger bony defects (1.5–2.0 cm), combination use with interconnected porous hydroxyapatite ceramic augmented with dense calcium hydroxyapatite was also useful.